2001
DOI: 10.1542/peds.108.2.e25
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication in Children: A Study From The Netherlands

Abstract: ABSTRACT. Objective. Although there is a global concern about the increased use of psychotropic agents in children, most research literature originates in the United States and is based on figures from the first half of the 1990s. Also, few studies document the use of various types of psychotropic agents. The objective of this study was to investigate the use of psychotropic medication in children in the Netherlands and to determine whether this corresponds with previously reported figures from the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
3
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 17 publications
7
79
3
1
Order By: Relevance
“…58 In The Netherlands, Schirm et al (2001) reported a five-fold increase in the use of stimulant medication among 0-19 years from 1995 to 1999. 59 The sharpest increases in NSW occurred in the mid-1990s. There are many factors that may have contributed to this, including: an increased public and clinician awareness and acceptance of ADHD as a disorder; a broadening of the diagnostic criteria for ADHD; a greater knowledge of the course of the disorder; an increase in the availability of ADHDspecific services, particularly paediatric and child psychiatric services; an increase in knowledge about the use and effectiveness of stimulant medication; fewer interruptions in treatment because of reduced concerns about growth retardation; lengthier periods of treatment; and an increase in the use of stimulant medication for the treatment of adults.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…58 In The Netherlands, Schirm et al (2001) reported a five-fold increase in the use of stimulant medication among 0-19 years from 1995 to 1999. 59 The sharpest increases in NSW occurred in the mid-1990s. There are many factors that may have contributed to this, including: an increased public and clinician awareness and acceptance of ADHD as a disorder; a broadening of the diagnostic criteria for ADHD; a greater knowledge of the course of the disorder; an increase in the availability of ADHDspecific services, particularly paediatric and child psychiatric services; an increase in knowledge about the use and effectiveness of stimulant medication; fewer interruptions in treatment because of reduced concerns about growth retardation; lengthier periods of treatment; and an increase in the use of stimulant medication for the treatment of adults.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the number and proportion of girls on medication has been observed overseas. 55,59 As a greater understanding and acceptance of ADHD has occurred over time, a greater number of girls may have been recognised as having the disorder and referred for treatment. The disproportionate growth in girls on psychostimulant therapy is likely to continue in the future if it is accepted that the prevalence rate of ADHD for girls in Australia is about half of that for boys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Second, the trend of increased psychotropic use has been observed among children less than 6 years old, 15,16 although others suggest that treatment in this age group is initiated only in conjunction with psychosocial services in children with predisposing risk factors. 17 More recent studies have demonstrated a continued rise in the use of psychotropics among children and adolescents both in the United States [3][4][5]18,19 and in Europe, 20,21 and these trends are seen for psychostimulants 3,4 and ADs. 5,19,20 However, there is much less data among Canadian children.…”
mentioning
confidence: 99%